Society’s Participation Model For Mangrove Rehabilitation in Cempa District, Pinrang Regency - Azmi, Nurul (Universitas Negeri Makassar, 2018)
This study aims to determine: 1) The level of society support in the rehabilitation of mangrove forests. 2) Model ofsociety participation in the rehabilitation of mangrove forests. The population in this study was 721 people, a sample was72 people. The sampling technique used is proportional random sampling. Data collection using observation techniques, interviews, and questionnaires. Data analysis using descriptive interpretative. The results showed that the level of knowledge and society support about mangrove forest rehabilitation is good enough. The model of societyÂ participation is that they are directly involved in the rehabilitation of mangrove forest starting from the planning stage, which is to provide aspirations in the form of concepts, ideas. Designing the concept to be implemented. Planting, they participates in the provision of seeds and planting. Establish working groups led by community leaders or chairmen of working groups. Maintenance, participate in mangrove csssare from the re-planting of mangroves that diaman dead and eradicate the pests that attack the mangrove seeds, and finally the Supervision, in this stageÂ they forbid anyone to remove, cut the mangrove that has been planted. The government also participates in the supervision and make the rule of giving sanctions to those who deliberately destroy the mangrove ecosystem.